'In search of lost time', 'friendship and archaeology': a personal reminiscence of Ludovic Mann, Joseph Harrison Maxwell and George Applebey – my father. (October 2020) - Applebey, George
Abstract : In this paper, I will reflect on my personal memories of Ludovic Mann, friend and mentor to my late father George Applebey, whose archaeological career is also a focus of the paper. They both worked together on Mann's most famous excavations at Knappers Farm, and the nearby painting of the Cochno Stone rock-art panel. However, these are only two examples of their long-term collaboration and friendship, and this paper will explore the broader context within which they worked. This will include consideration of other collaborators, such as J Harrison Maxwell, part of the 'Ludovic Group' in the first half of the twentieth century. The important role that all three men played in the development of Scottish archaeology is noted. The paper concludes with developments following Mann's death in 1955 including George Applebey's emergence as a noted amateur archaeologist in his own right, and the fate of the Mann and Applebey collections.